Carbon template with three-dimensional ordered through pore channels and application of carbon template in preparation of hierarchical pore SSZ-13 molecular sieve

By developing a new carbon template with three-dimensional orderly through-channels and using this template to prepare grade pore SSZ-13 molecular sieve, the problems of grade pore molecular sieve are solved in the prior art, and the preparation of molecular sieve with excellent performance is achieved.

CN119774581APending Publication Date: 2025-04-08WUHAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411966310.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing grade pore molecular sieves have limited problems in the diffusion of reactants and products, and the pore distribution of traditional soft template methods is disordered and has poor adjustability.

Method used

A new carbon template with three-dimensional orderly through-channel was developed, and a grade-pore SSZ-13 molecular sieve with excellent performance was prepared by the hard template method. The carbon template is self-assembled and carbonized by evaporation of polystyrene spheres and sucrose under dilute sulfuric acid medium to form a macroporous structure, and then undergoes high-temperature heat treatment under a protective atmosphere.

Benefits of technology

The pore penetration and tunability of grade pore SSZ-13 molecular sieve has been greatly improved, which solves the problem of limited diffusion of reactants and products, and simplifies the preparation process of carbon templates and shortens the preparation time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774581A_ABST
    Figure CN119774581A_ABST
Patent Text Reader

Abstract

The invention relates to a carbon template with three-dimensional ordered through pore channels and application of the carbon template in preparation of a hierarchical pore SSZ-13 molecular sieve. The preparation method comprises the following steps: firstly, mixing a PS pellet solution with cane sugar, then adding dilute sulphuric acid to carry out evaporation self-assembly and high-temperature carbonization, then carrying out pyrolysis in a protective atmosphere, and cooling to obtain a carbon template with three-dimensional ordered through pore channels; mixing an aluminum source, a silicon source, a mineralizing agent, a structure-directing agent and a solvent, uniformly mixing the obtained precursor solution with the carbon template, and sequentially carrying out aging, hydrothermal crystallization and roasting treatment to obtain a hierarchical porous SSZ-13 molecular sieve; and repeatedly mixing the hierarchical pore SSZ-13 molecular sieve with an ammonium nitrate solution, carrying out ammonium exchange, and drying to finally obtain the hierarchical pore SSZ-13 molecular sieve with through pore channels. By introducing the adjustable carbon template with through pore channels, the three-dimensional ordered pore channels are formed in the molecular sieve crystal, and meanwhile, the problem that diffusion of reactants and products is limited and the problems that pore channels formed by a traditional soft template method are disordered in distribution and poor in adjustability are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of new materials, in particular to the technical field of molecular sieve materials, and specifically to a carbon template with three-dimensional ordered through-holes and an application thereof in preparing hierarchical pore SSZ-13 molecular sieves. Background Art

[0002] SSZ-13 molecular sieve is a kind of small pore molecular sieve with CHA structure and pore size of 0.38nm. SSZ-13 molecular sieve can not only be used in methanol to olefins (MTO) reaction to obtain a high proportion of light olefins, but also can be loaded with metal Cu to prepare Cu-based SSZ-13 molecular sieve, which can then be used in the field of denitrification. In addition, the separation membrane made of SSZ-13 molecular sieve can also be used for the separation of methane / carbon dioxide. Although the unique structure of SSZ-13 molecular sieve gives it excellent product selectivity, it also brings problems such as limited diffusion of reactants and products.

[0003] At present, the synthesis routes of hierarchical pore molecular sieves including SSZ-13 molecular sieve are mainly divided into structure destruction method and structure construction method. Among them, the structure destruction method includes methods such as dealumination and desiliconization. This method generally causes great damage to the skeleton of the molecular sieve. For example, dealumination is at the expense of the acidic center of the molecular sieve, which will also affect the catalytic performance of the molecular sieve to a certain extent. The structure construction method mainly includes soft template method and hard template method. This method has almost no effect on the skeleton and crystallinity of the molecular sieve. The central idea of ​​the soft template method is the template mechanism, that is, using cationic polymers, cationic surfactant molecules and organosilane macromolecules as template agents, and using the supramolecular structure micelles formed in the solution as templates. Through the sol-gel process, under the guidance of the interaction between organic and inorganic species, self-assemble to form porous materials with narrow pore size distribution and regular and orderly pore structure. The literature (ACS Catalysis 2016, 6, (4): 2163-2177) reported a diquaternary ammonium salt surfactant (C22-4-4Br2) as a mesoporous pore-forming agent for molecular sieve synthesis. The diquaternary ammonium salt has a hydrophilic group at one end, which has a strong interaction with the molecular sieve framework, and a long carbon chain at the other end is a hydrophobic group, which is used to inhibit the growth of molecular sieve crystals, thereby preparing SSZ-13 molecular sieves with microporous-mesoporous multi-level pores. Analysis shows that the molecular sieves prepared by this method have poor mesoporous penetration and adjustability, and cannot be precisely controlled. There is still great resistance to the diffusion of reactants and products.

[0004] The hard template method is currently the most commonly used method for preparing hierarchical pore molecular sieves. This method usually adds a hard template to the microporous molecular sieve synthesis system, uses the existing ordered pore structure in the template to crystallize at a certain temperature for a period of time, and then removes the solid hard template to finally obtain a hierarchical pore molecular sieve material with complementary structure. Obviously, the key to the hard template method lies in the selection of the hard template. Previously, our team had developed an ordered macroporous-mesoporous multi-level porous carbon material, and used it as a hard template to prepare an ordered macroporous-mesoporous multi-level porous silicon-aluminum molecular sieve ZSM-5 single crystal with an opal structure (see Chinese patent CN106283187B). On this basis, we have developed a carbon template with a new structure and used it to solve the problems of limited diffusion of reactants and products of SSZ-13 molecular sieve. Summary of the invention

[0005] One of the purposes of the present invention is to provide a novel carbon template having three-dimensional ordered through-hole channels, wherein the size of the carbon template particles is (150-650) nm and the specific surface area is (500-800) m 2 / g, external specific surface area is (20-70)m 2 / g, micropore volume is (0.2-0.4)cm 3 / g, mesopore volume is (0.05-0.30)cm 3 / g.

[0006] The second object of the present invention is to provide a method for preparing the above-mentioned carbon template, comprising: mixing a polystyrene ball solution with sucrose evenly, then adding dilute sulfuric acid for evaporation self-assembly and carbonization, and then performing high-temperature heat treatment under a protective atmosphere, to finally obtain a carbon template with three-dimensional ordered through-holes.

[0007] Furthermore, the concentration of the polystyrene bead solution is 6.5wt%-13.5wt%, preferably 10wt%.

[0008] Furthermore, the concentration of the dilute sulfuric acid is 2wt%-50wt%, preferably 10wt%.

[0009] Furthermore, the mass ratio of polystyrene beads, sucrose and sulfuric acid required for the reaction is 1:0.06-0.36:0.1-1, preferably 1:0.15:0.15.

[0010] Furthermore, the temperature of the evaporation self-assembly is 60-100°C.

[0011] Furthermore, the carbonization temperature is 90-160°C.

[0012] Furthermore, the carbonized solid is transferred to a tube furnace and subjected to high temperature heat treatment under a protective atmosphere, wherein the protective atmosphere is any one of nitrogen, helium and argon, and the high temperature heat treatment temperature is 550-650°C.

[0013] The third object of the present invention is to provide a method for preparing a hierarchical pore SSZ-13 molecular sieve using the above-mentioned carbon template, comprising: mixing an aluminum source, a silicon source, a mineralizer, a structure directing agent, and a solvent to obtain a precursor solution, mixing the precursor solution with the carbon template to obtain a mixture that is subjected to aging, hydrothermal crystallization, and calcination to finally obtain a hierarchical pore SSZ-13 molecular sieve.

[0014] Furthermore, the aluminum source is selected from at least one of aluminum isopropoxide, sodium aluminate, aluminum oxide, pseudo-boehmite, aluminum sulfate, and aluminum hydroxide.

[0015] Furthermore, the silicon source is selected from at least one of tetraethyl silicate, fumed silica, and silica sol.

[0016] Furthermore, the mineralizer is selected from at least one of ammonium chloride and ammonium fluoride.

[0017] Furthermore, the structure directing agent is selected from at least one of N,N,N-trimethyl-1-adamantyl ammonium hydroxide, benzyltrimethylammonium, N,N,N-dimethylethylcyclohexyl ammonium bromide, tetraethylammonium hydroxide, choline chloride, and Cu-tetraethylenepentamine.

[0018] Furthermore, the solvent is selected from at least one of deionized water, ultrapure water and distilled water.

[0019] Furthermore, the molar ratio of the aluminum source (denoted as Al2O3), the silicon source (denoted as SiO2), the mineralizer, the structure directing agent, and the solvent in the precursor solution is 1:0.01-0.1:0.05-0.2:0.1-0.9:10-35.

[0020] Furthermore, the mass ratio of the precursor solution to the carbon template when mixed is 1:0.5-3.

[0021] Furthermore, the aging is carried out in an oven, the aging temperature is 60-100° C., and the aging time is 6-48 hours.

[0022] Furthermore, the hydrothermal crystallization is carried out in a reaction kettle, the hydrothermal crystallization temperature is 140-180° C., and the hydrothermal crystallization time is 72-144 h.

[0023] Furthermore, the calcination is carried out in a muffle furnace, the calcination temperature is 480-720° C., the calcination time is 1-10 hours, the calcination atmosphere is air, and the calcination is completed and the furnace is cooled to room temperature.

[0024] Furthermore, the preparation method also includes an ammonium exchange treatment, and the specific process is as follows: the prepared graded pore SSZ-13 molecular sieve is added to an ammonium nitrate solution, the resulting mixture is heated to 50-100°C and fully allowed to stand, the solid is washed and dried after solid-liquid separation, the above operation is repeated multiple times, and the obtained solid is heated to 480-680°C in an air atmosphere for calcination, and after cooling, a graded pore SSZ-13 molecular sieve with through pores is obtained. The purpose of the ammonium exchange here is to convert Na + Type molecular sieve exchange to H + type molecular sieve, making it catalytically active.

[0025] Compared with existing similar products or technologies, the advancement of this invention is mainly reflected in the following aspects:

[0026] (1) A carbon template with three-dimensional ordered through-hole channels was synthesized, which has the advantages of uniform size, abundant pores, interconnected channels, and large specific surface area. More importantly, the carbon template contains only large pores, which can ensure that the synthesized molecular sieve crystals are single crystals without any small particles.

[0027] (2) The hierarchical pore SSZ-13 molecular sieve with excellent performance was prepared using the newly synthesized carbon template, which solved the problems of disordered pore distribution and poor pore adjustability that are common in the traditional soft template method.

[0028] (3) The preparation process of the carbon template is simplified, eliminating the complicated and tedious programmed temperature rising steps, and only one step of carbonization is required, which greatly shortens the time required to prepare the template. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The XRD spectra of the molecular sieves prepared in Examples 1-3 and Comparative Example 1 are shown.

[0030] Figure 2 This is a SEM image of the carbon template prepared in Example 1.

[0031] Figure 3 This is a SEM photograph of the hierarchical pore SSZ-13 molecular sieve prepared in Example 1.

[0032] Figure 4 Graph showing nitrogen adsorption test results of the molecular sieves prepared in Examples 1-3 and Comparative Example 1.

[0033] Figure 5 This is a graph showing the MTO catalytic test results of the molecular sieves prepared in Examples 1-3 and Comparative Example 1. DETAILED DESCRIPTION

[0034] In order to enable ordinary technicians in the field to fully understand the technical solutions and beneficial effects of the present invention, the following is a further detailed description in conjunction with specific embodiments and drawings.

[0035] Example 1

[0036] 40g of polystyrene beads with a size of 200nm were added to 360g of deionized water to obtain a polystyrene bead solution with a concentration of 10wt%. 6g of sucrose was added to the polystyrene bead solution and stirred for 5min, followed by dropwise addition of 6g of a 10wt% dilute sulfuric acid solution and stirring for 10min. The resulting mixture was transferred to an 80°C oven and allowed to stand for 6-24h for evaporation self-assembly, followed by heating to 110°C and keeping warm for 6h to fully carbonize it. The carbonized solid sample was transferred to a tubular furnace, heated to 550-650°C in a nitrogen atmosphere and kept warm for 7h to fully pyrolyze the polystyrene beads, and finally cooled to room temperature with the furnace to obtain a carbon template with a pore size of 200nm and a three-dimensional ordered through-hole channel.

[0037] 13.58g N,N,N-trimethyl-1-adamantyl ammonium hydroxide was mixed with 7.85g deionized water, and then 0.164g ammonium chloride was added and stirred until it was clear, followed by 0.41g aluminum isopropoxide and stirred for 1h to completely dissolve it, and finally 8.33g tetraethyl silicate was added and stirred for more than 4h to completely hydrolyze it, and the resulting mixture was the precursor gel. According to a mass ratio of 1:1, the precursor gel and the carbon template prepared in the previous step were mixed evenly, and the resulting mixture was heated to 80°C and aged overnight to obtain a mixture dry gel. The mixture dry gel was transferred to a polytetrafluoroethylene-lined hydrothermal reactor, and the reactor was heated to 160°C and kept for hydrothermal crystallization for 120 hours. After the hydrothermal crystallization was completed, it was centrifuged and washed with water until neutral, and then transferred to an 80°C oven for overnight drying. The dried solid was transferred to a muffle furnace, heated to 600° C. in an air atmosphere and calcined for 7 hours to completely remove the template agent, thereby obtaining a hierarchical pore SSZ-13 molecular sieve with through-pores.

[0038] According to the mass ratio of 1:10, the obtained hierarchical pore molecular sieve was mixed with an ammonium nitrate solution with a concentration of 1 mol / L, and the obtained mixture was heated to 80°C for ammonium exchange for 2 hours, and then filtered and the solid was placed at 100°C for full drying. Repeat the ammonium exchange-filtration-drying three times, and finally, the obtained solid product was heated from room temperature to 550°C at a heating rate of 2-10°C / min in an air atmosphere and calcined for 7 hours. After the calcination was completed, it was cooled to room temperature at a cooling rate of 2-10°C / min, and finally the hierarchical pore SSZ-13 molecular sieve with through pores was obtained.

[0039] Example 2

[0040] 40g of polystyrene beads with a size of 400nm were added to 360g of deionized water to obtain a polystyrene bead solution with a concentration of 10wt%. 6g of sucrose was added to the polystyrene bead solution and stirred for 5min, followed by dropwise addition of 6g of a 10wt% dilute sulfuric acid solution and stirring for 10min. The resulting mixture was transferred to an 80°C oven and allowed to stand for 6-24h for evaporation and self-assembly, and then heated to 110°C for 6h to fully carbonize. The carbonized solid sample was transferred to a tubular furnace, heated to 550-650°C in a nitrogen atmosphere and pyrolyzed for 7h, and finally cooled to room temperature with the furnace to obtain a carbon template with a pore size of 400nm and a three-dimensional ordered through-hole channel.

[0041] 13.58g N,N,N-trimethyl-1-adamantyl ammonium hydroxide was mixed with 7.85g deionized water, and then 0.164g ammonium chloride was added and stirred until it was clear, followed by adding 0.41g aluminum isopropoxide and stirring for 1h to completely dissolve it, and finally 8.33g tetraethyl silicate was added and stirred for at least 4h to completely hydrolyze it to obtain a precursor gel. According to a mass ratio of 1:1, the precursor gel and the carbon template prepared in the previous step were mixed evenly, and the resulting mixture was heated to 80°C and aged overnight to obtain a mixture dry gel. The mixture dry gel was transferred to a polytetrafluoroethylene-lined hydrothermal reactor, and the reactor was heated to 160°C and hydrothermally crystallized for 120 hours. After the hydrothermal crystallization was completed, it was centrifuged and washed with water until neutral, and then placed in an 80°C oven to dry overnight. The dried solid was transferred to a muffle furnace, heated to 600°C in an air atmosphere, and calcined for 7 hours to obtain a hierarchical pore SSZ-13 molecular sieve with through-holes.

[0042] The obtained hierarchical pore molecular sieve was mixed with an ammonium nitrate solution with a concentration of 1 mol / L at a mass ratio of 1:10, and the obtained mixture was heated to 80°C for ammonium exchange for 2 hours, and then filtered and the solid was fully dried at 100°C. The ammonium exchange-filtration-drying process was repeated three times, and finally the solid product was heated from room temperature to 550°C at a heating rate of 2-10°C / min in an air atmosphere and calcined for 7 hours. After the calcination was completed, it was cooled to room temperature at a cooling rate of 2-10°C / min, and finally the hierarchical pore SSZ-13 molecular sieve with through pores was obtained.

[0043] Example 3

[0044] 40g of polystyrene beads with a size of 600nm were added to 360g of deionized water to obtain a polystyrene bead solution with a concentration of 10wt%. 6g of sucrose was added to the polystyrene bead solution and stirred for 5min, followed by dropwise addition of 6g of a 10wt% dilute sulfuric acid solution and stirring for 10min. The resulting mixture was transferred to an 80°C oven and allowed to stand for 6-24h for evaporation self-assembly, followed by heating to 110°C and keeping warm for 6h to fully carbonize it. The carbonized solid sample was transferred to a tubular furnace, heated to 550-650°C in a nitrogen atmosphere and kept warm for 7h for pyrolysis, and finally cooled to room temperature with the furnace to obtain a carbon template with a pore size of 600nm and a three-dimensional ordered through-hole channel.

[0045] 13.58g N,N,N-trimethyl-1-adamantyl ammonium hydroxide was mixed with 7.85g deionized water, and then 0.164g ammonium chloride was added and stirred until it was clear, followed by adding 0.41g aluminum isopropoxide and stirring for 1h to completely dissolve it, and finally 8.33g tetraethyl silicate was added and stirred for at least 4h to completely hydrolyze it to obtain a precursor gel. According to a mass ratio of 1:1, the precursor gel and the carbon template prepared in the previous step were mixed evenly, and the resulting mixture was heated to 80°C and aged overnight to obtain a mixture dry gel. The mixture dry gel was transferred to a polytetrafluoroethylene-lined hydrothermal reactor, and the reactor was heated to 160°C and hydrothermally crystallized for 120 hours. After the hydrothermal crystallization was completed, it was centrifuged and washed with water until neutral, and then transferred to an 80°C oven to dry overnight. The dried solid was transferred to a muffle furnace, heated to 600°C in an air atmosphere, and calcined for 7 hours to obtain a hierarchical pore SSZ-13 molecular sieve with through-holes.

[0046] According to the mass ratio of 1:10, the obtained hierarchical pore molecular sieve was mixed with an ammonium nitrate solution with a concentration of 1 mol / L, and the obtained mixture was heated to 80°C for ammonium exchange for 2 hours, and then filtered and the solid was placed at 100°C for full drying. Repeat the ammonium exchange-filtration-drying three times, and finally, the obtained solid product was heated from room temperature to 550°C at a heating rate of 2-10°C / min in an air atmosphere and calcined for 7 hours. After the calcination was completed, it was cooled to room temperature at a cooling rate of 2-10°C / min, and finally the hierarchical pore SSZ-13 molecular sieve with through pores was obtained.

[0047] Example 4

[0048] This embodiment is basically the same as embodiment 1, except that the aluminum source is changed from aluminum isopropoxide to sodium aluminate, the silicon source is changed from tetraethyl silicate to fumed silica, the mineralizer is still ammonium chloride, and the structure directing agent is changed from N,N,N-trimethyl-1-adamantyl ammonium hydroxide to benzyltrimethylammonium, and the molar ratio of the four is 1:0.01-0.1:0.05-0.2:0.1-0.9:10-35.

[0049] Example 5

[0050] This embodiment is basically the same as embodiment 1, except that the aluminum source is changed from aluminum isopropoxide to aluminum oxide, the silicon source is changed from tetraethyl silicate to silica sol, the mineralizer is changed from ammonium chloride to ammonium fluoride, and the structure directing agent is changed from N,N,N-trimethyl-1-adamantyl ammonium hydroxide to N,N,N-dimethylethylcyclohexyl ammonium bromide, and the molar ratio of the four is 1:0.01-0.1:0.05-0.2:0.1-0.9:10-35.

[0051] Example 6

[0052] This embodiment is basically the same as Embodiment 1, except that the aluminum source is changed from aluminum isopropoxide to aluminum hydroxide, the silicon source is still tetraethyl silicate, the mineralizer is still ammonium chloride, the structure directing agent is changed from N,N,N-trimethyl-1-adamantyl ammonium hydroxide to tetraethyl ammonium hydroxide, and the molar ratio of the four is 1:0.01-0.1:0.05-0.2:0.1-0.9:10-35.

[0053] Comparative Example 1

[0054] 4.227g N,N,N-trimethyl-1-adamantyl ammonium hydroxide was mixed with 9.63g deionized water, and then 0.5106g aluminum isopropoxide was added and stirred for 1h to completely dissolve it, followed by adding 10g As-30 silica sol and stirring for 6h to obtain a precursor solution. The precursor solution was transferred to a polytetrafluoroethylene-lined reactor, which was heated to 160°C and kept for hydrothermal crystallization for 4 days. After the hydrothermal crystallization, it was washed with water by centrifugation until neutral, and then transferred to an 80°C oven for overnight drying. The dried solid was transferred to a muffle furnace, heated to 600°C in an air atmosphere, and kept warm for 7 hours to finally obtain a microporous SSZ-13 molecular sieve.

[0055] The prepared microporous SSZ-13 molecular sieve was mixed with an ammonium nitrate solution with a concentration of 1 mol / L at a mass ratio of 1:10, and the obtained mixture was heated to 80°C for ammonium exchange for 2 hours, and then filtered and the solid was placed at 100°C for full drying. The ammonium exchange-filtration-drying was repeated three times, and finally the obtained solid product was heated from room temperature to 550°C at a heating rate of 2-10°C / min in an air atmosphere and calcined for 7 hours. After the calcination was completed, it was cooled to room temperature at a cooling rate of 2-10°C / min to finally obtain H + Type microporous SSZ-13 molecular sieve.

[0056] In order to fully understand the structure and performance of the SSZ-13 molecular sieves prepared in Examples 1-3 and Comparative Example 1, samples were taken and the following tests were performed:

[0057] (1) XRD test

[0058] The X-ray diffraction analysis instrument used was a Bruker X-ray diffractometer D8Advance equipped with CuKα radiation (X-ray wavelength ), the test conditions are: test tube voltage 40 kV, test tube current 40 mA, scanning range 2θ = 5-45°, scanning speed step = 0.05° / s.

[0059] The XRD test results of the final product SSZ-13 molecular sieve obtained in Examples 1-3 and Comparative Example 1 are as follows: Figure 1 As shown in the figure, it can be seen that the XRD spectra of the products obtained in Examples 1-3 and Comparative Example 1 are consistent with the characteristic spectra of SSZ-13, which indicates that all samples are pure phase SSZ-13 molecular sieves.

[0060] (2) SEM test

[0061] The SEM photos of the carbon template and the hierarchical pore SSZ-13 molecular sieve with through-holes prepared in Example 1 are shown as follows: Figure 2-3 As shown. Figure 2 It can be seen that the pore size of the carbon template is 200nm, which is basically consistent with the particle size of PS. Figure 3 It can be seen that the structural unit particle size of the hierarchical pore SSZ-13 molecular sieve synthesized using the macroporous carbon as a template is about 200nm, and the structural units are face-centered cubic stacking.

[0062] (3) Specific surface area and pore size distribution test

[0063] The SSZ-13 molecular sieve samples prepared in Examples 1-3 and Comparative Example 1 were characterized by nitrogen physical adsorption using a Micromeritics ASAP 2020 nitrogen physical adsorption instrument. The samples were pretreated before analysis in the following manner: each molecular sieve was placed in a quartz tube, which was then evacuated and heated to 300°C at a heating rate of 10°C / min, and the evacuation was continued for 12 hours.

[0064] Table 1 Comparison of microstructure parameters of different SSZ-13 molecular sieve samples

[0065]

[0066] The results of nitrogen adsorption test are shown in Table 1. Figure 4 By comparison, it is found that the introduction of hierarchical channels increases the specific surface area and mesopore volume of the molecular sieve, which can effectively improve the diffusion and flow properties of the products and reactants.

[0067] (4) MTO catalytic performance test

[0068] The SSZ-13 molecular sieve samples prepared in Examples 1-3 and Comparative Example 1 were tableted and then crushed to 40-60 mesh to obtain catalyst particles. 0.1 g of catalyst particles were weighed and loaded into a fixed bed reactor for MTO performance evaluation. Nitrogen was activated at 500°C for 1 hour, then cooled to 400°C, methanol was carried by nitrogen, the nitrogen flow rate was 15 mL / min, and the methanol weight space velocity was 1 h. -1 The obtained product was analyzed by gas chromatograph (GC-2014C), and the results are shown in Table 2. Figure 5 shown.

[0069] Table 2 Comparison of catalytic performance of different SSZ-13 molecular sieve samples

[0070]

[0071] Note: = represents olefins, + represents all products containing 5 or more carbon atoms.

[0072] From Table 2, Figure 5 It can be seen that compared with Comparative Example 1, the hierarchical pore SSZ-13 molecular sieve samples prepared in Examples 1-3 have a longer lifespan, and the product distribution is basically the same.

Claims

1. A carbon template having three-dimensional ordered through-hole channels, characterized in that: The size of the carbon template is 150-650nm and the specific surface area is 500-800m 2 / g, external specific surface area is 20-70m 2 / g, micropore volume is 0.2-0.4cm 3 / g, and the mesopore volume is 0.05-0.30cm 3 / g.

2. The method for preparing the carbon template according to claim 1, characterized in that The method comprises: uniformly mixing a polystyrene ball solution with sucrose, adding dilute sulfuric acid for evaporation self-assembly and carbonization, and then performing high-temperature heat treatment under a protective atmosphere to obtain a carbon template with three-dimensional ordered through-holes.

3. The method according to claim 2, characterized in that: The mass ratio of polystyrene beads, sucrose and sulfuric acid required for the reaction is 1:0.06-0.36:0.1-1.

4. The method according to claim 2, characterized in that: The temperature of evaporation self-assembly is 60-100°C, and the temperature of carbonization is 90-160°C.

5. The method according to claim 2, characterized in that: The carbonized solid is subjected to high-temperature heat treatment under a protective atmosphere, wherein the protective atmosphere is selected from any one of nitrogen, helium and argon, and the temperature of the high-temperature heat treatment is 550-650°C.

6. A method for preparing hierarchical pore SSZ-13 molecular sieve using the carbon template of claim 1, characterized in that The method comprises: uniformly mixing an aluminum source, a silicon source, a mineralizer, a structure directing agent and a solvent to obtain a precursor solution, uniformly mixing the precursor solution and the carbon template, and then performing aging, hydrothermal crystallization and calcination treatments to obtain a hierarchical pore SSZ-13 molecular sieve.

7. The method according to claim 6, characterized in that: The aluminum source is selected from at least one of aluminum isopropoxide, sodium aluminate, alumina, pseudo-boehmite, aluminum sulfate, and aluminum hydroxide; the silicon source is selected from at least one of tetraethyl silicate, fumed silica, and silica sol; the mineralizer is selected from at least one of ammonium chloride and ammonium fluoride; the structure directing agent is selected from at least one of N,N,N-trimethyl-1-adamantyl ammonium hydroxide, benzyltrimethylammonium, N,N,N-dimethylethylcyclohexyl ammonium bromide, tetraethylammonium hydroxide, choline chloride, and Cu-tetraethylenepentamine; and the solvent is selected from at least one of deionized water, ultrapure water, and distilled water.

8. The method according to claim 6, characterized in that: The molar ratio of the aluminum source (denoted as Al2O3), silicon source (denoted as SiO2), mineralizer, structure directing agent and solvent in the precursor solution is 1:0.01-0.1:0.05-0.2:0.1-0.9:10-35, and the mass ratio of the precursor solution and the carbon template when mixed is 1:0.5-3.

9. The method according to claim 6, characterized in that: The aging temperature is 60-100°C, and the aging time is 6-48h; the hydrothermal crystallization temperature is 140-180°C, and the hydrothermal crystallization time is 72-144h; the roasting temperature is 480-720°C, and the roasting time is 1-10h. The roasting atmosphere is air, and the furnace is cooled to room temperature after roasting.

10. The method according to claim 6, characterized in that: The preparation method also includes an ammonium exchange treatment, and the specific process is as follows: adding the prepared graded pore SSZ-13 molecular sieve to an ammonium nitrate solution, then heating it to 50-100° C. and fully standing it, washing and drying the obtained solid after solid-liquid separation, repeating the above operation multiple times, heating the finally obtained solid to 480-680° C. in an air atmosphere and fully calcining it, and cooling it to obtain the graded pore SSZ-13 molecular sieve with through pores.

Citation Information

Patent Citations

  • A single crystal of ZSM-5, an ordered macroporous-mesoporous hierarchical porous silica-alumina molecular sieve with an opal structure, and its synthesis method.

    CN106283187B